Pengenalan Wirausaha Sejak Dini dan Aplikasi Dompet Digital terhadap Generasi Alpha Desa Kepayang, Kecamatan Anjongan, Kabupaten Mempawah, Provinsi Kalimantan Barat - Riastifa, Ririn Nur; Purmono, Bintoro Bagus; Constantine, Angwen; Sen, Doflin; Najmi, Bimewahqi; Rachman, Haikal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This Community Service Program (KKM-PKM) aims to introduce early entrepreneurship and the use of digital wallet applications to Generation Alpha in Kepayang Village. With the rapid advancement of technology and changing patterns in economic behavior, it is crucial for young generations, especially Generation Alpha, to understand entrepreneurship and financial technology skills, such as digital wallets, which are increasingly relevant in daily life. Through an interactive and practical educational approach, this activity involved elementary school students in Kepayang Village. The program included basic entrepreneurship training, covering identifying business opportunities, simple financial management, and simulations of using digital wallet applications like OVO, GoPay, and Dana. The program's results showed high enthusiasm from the participants and an increased understanding of the importance of entrepreneurship and digital wallets in everyday life. It is hoped that this initiative will equip Generation Alpha with relevant skills to face future economic challenges.